Խոշոր եղջերավոր կենդանիների բաբեզիոզի բուժկանխարգելիչ միջոցառումները - Գրիգորյան, Վալերի; Պետրոսյան, Գայանե; Երիբեկյան, Սպարտակ; Գրիգորյան, Լիանա (ՀԱԱՀ հիմնադրամ)
Бабезиоз крупного рогатого скота – широко распространенное в Армении сезонное трансмиссивное заболевание. Цель исследования – изучение влияния возбудителей бабезиоза на показатели крови животных, сравнение эффективности различных методов диагностики и одновременно проведение лечебно-профилактических мероприятий с использованием наиболее эффективных препаратов. У больных бабезиозом животных изменяется соотношение форменных элементов крови, снижается количество эритроцитов и гемоглобина, увеличивается число лейкоцитов. Наиболее эффективным методом диагностики заболевания является исследование на основе полимеразной цепной реакции. В целях профилактики необходимо проводить агромелиоративные мероприятия, использовать инсектициды, производить обработку и дезинфекцию животных. Bovine babesiosis is a widespread, seasonal, vector-borne disease in the Republic of Armenia. The primary vectors responsible for transmission are pasture ticks of the Rhipicephalus genus. A notable characteristic of the babesi-osis pathogen's life cycle is its transovarial transmission — from an infected, sexually mature tick to its larvae — allowing the pathogen to persist across multiple tick generations. Consequently, tick habitats serve as potential sites for the infection of livestock. When animals are housed in a manger, the risk of babesiosis infection is significantly reduced due to limited exposure to ticks. The objective of this study is to examine the impact of babesiosis pathogens on bovine hematological parameters, compare the efficacy of various diagnostic methods, and simultaneously identify the most effective pharma-ceutical treatments and preventive measures. Bovine babesiosis alters the composition of blood elements: red blood cell count and hemoglobin levels decrease, while white blood cell count increases. Polymerase Chain Reaction (PCR) testing is considered a highly effective diagnostic tool for detecting the disease.
Keywords: Անասնաբուժական բժշկագիտություն և անասնաբուծություն